Investigation of DNA interaction and antiproliferative activity of mixed ligand dioxidomolybdenum(VI) complexes incorporating ONO donor aroylhydrazone ligands - Dinda, Rupam; Panda, Arpita; Banerjee, Atanu; Mohanty, Monalisa; Pasayat, Sagarika; Tiekink, Edward R. T. * (Elsevier, 2020)
Four new mixed ligand dioxidomolybdenum(VI) [MoVIO2L1-3(Q)] (1–3), [MoVIO2L4(Q)]2 (H2O) (4) [where Q = MeOH for 1 and imidazole for 2–4] complexes have been synthesized using four different ONO donor aroylhydrazone ligands (H2L1–4). All the derived ligands and complexes have been characterised by different physicochemical techniques, that is, elemental analysis, spectroscopic methods (UV–Vis, NMR and IR), and cyclic voltammetry. The molecular geometries of 1–4 were established by X-ray crystallography which reveals - - the Schiff base ligands coordinate - the distorted octahedral metal centres in a di-negative tridentate fashion. The complexes have shown moderate binding affinity (103 to 104 M−1) towards CT-DNA. Further, in vitro cytotoxicity activity of all the complexes were determined against HT-29 (colon cancer) and HeLa (cervical cancer) cell lines. Complex 4, due to the presence of a heterocyclic 2-hydroxy-1-naphthyl moiety in the ligand backbone, was found to be more biologically active in comparison to the others in the series.